International Women's Day rally - Chesterfield, 1985 (1985)
1985 1960-2000 "International Women's Day rally - Chesterfield, 1985" [T0545.jpg], 1985, Coates, Christine This woman is wearing a collection of badges from the 1984-85 Miners strike.